Offshoring of higher education services in strategic nets: A dynamic capabilities perspective - Butler, Bella; Soontiens, Werner (Pergamon, 2014)
We examine the process of the intentional transformation of a loose organic network into a strategic net within the context of offshoring higher education services over time. The study shows that this educational net is hub-driven by a large Australian university that acts as the network facilitator. Our results confirm the importance of the dynamic capabilities of both the net and its participants as drivers of the transformation from the network into the strategic net and the realization of a competitive advantage from offshoring. Our distinct contribution is that we bridge previous studies of the management of strategic nets and the dynamic capabilities view in a longitudinal study within a multi-country context characterized by ongoing regulatory changes.